Placental hypoxia: What have we learnt from small animal models?. (15th September 2021) - Siragher, Emma; Sferruzzi-Perri, Amanda N.
Abstract: Intrauterine hypoxia is a feature of pregnancy complications, both at high altitude and sea level. To understand the placental response to reduced oxygen availability, small animal models of maternal inhalation hypoxia (MIH) or reduced uterine perfusion pressure (RUPP) may be utilised. The aim of this review was to compare the findings of those studies to identify the role of oxygen availability in adapting placental structural and functional phenotypes in relation to fetal outcome. It also sought to explore the evidence for the involvement of particular genes and protein signalling pathways in the placenta in mediating hypoxia driven alterations. The data available demonstrate that both MIH and RUPP can induce placental hypoxia, which affects placental structure and vascularity, as well as glucose, amino acid, calcium and possibly lipid transport capacity. In addition, changes have been observed in HIF, VEGF, insulin/IGF2, AMPK, mTOR, PI3K and PPARγ signalling, which may be key in linking together observed phenotypes under conditions of placental hypoxia. Many different manipulations have been examined, with varied outcomes depending on the intensity, timing and duration of the insult. Some manipulations have detrimental effects on placental phenotype, viability and fetal growth, whereas in others, the placenta appears to adapt to uphold fetal growth despite the challenge of low oxygen. Together these data suggest a complex response of the placenta to reduced oxygen availability, which links to changes in fetal outcomes. However, further work is required to explore the role of fetal sex, altered maternal physiology and placental molecular mechanisms to fully understand placental responses to hypoxia and their relevance for pregnancy outcome. Highlights: Maternal inhalation hypoxia or uterine artery ligation can induce placental hypoxia. Comparison between animal models informs on the functions of oxygen in the placenta. Placental hypoxia alters transport, metabolism, vascularity and endocrine function. Interaction between signalling pathways induces structural and functional alterations. Insult timing, maternal physiology and fetal sex modify hypoxic placenta phenotype.